The Influence of Raudhatul Athfal RA Teachers' Pedagogic Competence on Handling Children with Learning Difficulties in Seberang Ulu District, Palembang - Yuniliyanti, Yuniliyanti; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to determine the Pedagogical Competence of Raudhatul Athfal (RA) Teachers in handling Children with Learning Disabilities in Seberang Ulu District, Palembang City. The researcher used a quantitative method (survey) by distributing questionnaires to RA teachers in Seberang Ulu District, Palembang City. With a sample of 72 RA teachers, the results showed that the level of Pedagogical Competence of Raudhatul Athfal (RA) Teachers in handling Children with Learning Disabilities in Seberang Ulu District, Palembang City was in the "Medium" category of 49.33% (37 teachers), "Low" of 36% (27 teachers), and "High" of 14.67% (11 teachers). Based on the average value, which is 3.28%, the level of Pedagogical Competence of RA Teachers in handling Children with Learning Disabilities in Seberang Ulu District, Palembang City is in the "MEDIUM" category.